2018
DOI: 10.1002/jtr.2238
|View full text |Cite
|
Sign up to set email alerts
|

Self‐congruity and motivations as antecedents of destination perceived value: The moderating effect of previous experience

Abstract: The present research proposes and validates a model in which tourist motivations and self‐congruity with the destination are considered antecedents of the perceived value of that destination and in which the tourist's previous experience of the destination exerts an important moderating effect. This model is estimated using partial least squares path modelling, based on a sample of 503 British tourists visiting Spain. The findings show that a high level of self‐congruity between the tourist and the destination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 88 publications
2
18
0
Order By: Relevance
“…Follow-up research has continuously improved the definition and characteristics of perceived value (Chen & Tsai, 2007). This concept is also used in the field of tourism and hospitality (Frías-Jamilena et al, 2019;Kim et al, 2015;Yen et al, 2018).…”
Section: Perceived Value and Brand Authenticitymentioning
confidence: 99%
“…Follow-up research has continuously improved the definition and characteristics of perceived value (Chen & Tsai, 2007). This concept is also used in the field of tourism and hospitality (Frías-Jamilena et al, 2019;Kim et al, 2015;Yen et al, 2018).…”
Section: Perceived Value and Brand Authenticitymentioning
confidence: 99%
“…It can be difficult to measure brand value for destinations. Some studies have measured it from the perspective of tourism experience [75]. Different measurement dimensions, in terms of price value, quality value, social value, and affective value, have been developed for the brand value of destinations [76].…”
Section: Brand Valuementioning
confidence: 99%
“…Moreover, studies in the tourism industry have found that selfcongruity has various effects on tourists' experiential value. For example, tourists' selfcongruity has an effect on their perceived value of a destination [52]. Based on the above, this study proposes the following hypothesis: Hypothesis 3 (H3).…”
Section: Self-congruencementioning
confidence: 91%